Dr. Auchmuty's letter to Capt. Montresor, chief engineer, at Boston : New-York, April 19, 1775. My dear sir, Yesterday Capt. Coupar arrived from London ; Rivington I conclude will have all the news in his paper . - Auchmuty, Samuel, 1722-1777 (LLMC-digital (Series), 1775)
Includes extracts from a letter concerning the unrest in the colonies; dated London, March the 4th, 1775.